Temperature and pressure dependence of volumetric properties for binary mixtures of n-heptane and n-octane - Pečar, Darja (Acta chimica slovenica, 2007)
The densities of n-heptane, n-octane and their binary mixtures were measured at 298.15, 323.15 and 348.15 K and within the pressure range 0.1 to 40 MPa using a vibrating tube densimeter. The reliability of this technique has been verified in our previous works. The partial molar volumes, excess molar volumes, isothermal compressibilities, isobaric thermal expansivities and internal pressures were calculated from the obtained densities. This study presents the dependence of densities, partial molar volumes, excess molar volumes, isothermal compressibilities, isobaric thermal expansivities and internal pressures on composition, temperature and pressure.
Keywords: fizikalna kemija; gostota; heptan; oktan; parcialna molska prostornina; razteznostni koeficient; stisljivost